2021
DOI: 10.1016/j.amsu.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 levels in patients with covid-19 with diabetic foot ulcers: A prospective study in southeast asia

Abstract: Background Viral infection can compound the severity of pre-existing inflammation caused by underlying diseases. For those with a chronic, immune-related condition such as diabetic foot ulcers (DFUs), the coronavirus disease (COVID-19) serves to exacerbate the inflammatory burden. Serum levels of intracellular adhesion molecule-1 (ICAM-1), a primary mediator of cell adhesion express in the inflammatory process, are often used to indicate the gravity of all inflammatory conditions. Therefore, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Patients with COVID-19 had elevated ICAM-1 level, which could aggravate the preexisting inflammation in patient with DFU. 26 During the pandemic, we also found that number of patients with osteomyelitis was higher than the pre-pandemic (72.6% vs 87.3%). Osteomyelitis could occur when infection from wound site spread contiguously to the bone.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Patients with COVID-19 had elevated ICAM-1 level, which could aggravate the preexisting inflammation in patient with DFU. 26 During the pandemic, we also found that number of patients with osteomyelitis was higher than the pre-pandemic (72.6% vs 87.3%). Osteomyelitis could occur when infection from wound site spread contiguously to the bone.…”
Section: Discussionmentioning
confidence: 57%
“…Patients with COVID-19 had elevated ICAM-1 level, which could aggravate the pre-existing inflammation in patient with DFU. 26 …”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 Pango lineage B.1.617.2, commonly known as the Delta variant, is a SARS-CoV-2 variant that was discovered in India on September 07, 2020. The Delta variant was declared as a variant of concern by the World Health Organization due to its high infectivity and has rapidly become a major variant in different regions globally [ [2] , [3] , [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…The first cases of coronavirus disease 2019 (COVID-19) were detected in Wuhan, China, on 31st December 2019 ( Zhou et al, 2020 ; Oley et al, 2021 ). It was subsequently confirmed that these cases were due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Coronaviridae Study Group of the International Committee on Taxonomy of Viruses, 2020 ), a respiratory virus that is highly transmissible between humans, and spread rapidly globally.…”
Section: Introductionmentioning
confidence: 99%